PENINGKATAN HASIL MELON (Cucumis melo L.) MELALUI PENGATURAN JARAK TANAM DAN JUMLAH BUAH - Zakaria, Heru; Sesanti, Rizka Novi; Maulida, Desi; Sismanto, Sismanto (Agros Journal of Agriculture Science, 2024)
The problems in melon cultivation include the decreasing availability of agricultural land and suboptimal productivity. To address these issues, a review of melon cultivation techniques is necessary, focusing on adjusting plant spacing and increasing the number of fruits per plant. This study aims to examine the effects of plant spacing and the number of fruits per plant on melon (Cucumis melo L.) production. The research was conducted on the horticultural land of Politeknik Negeri Lampung from June to September 2022. The experimental design used was a factorial Randomized Block Design (RBD) with two factors, each repeated three times. The first factor was plant spacing with three levels: 40 cm x 60 cm (J1), 60 cm x 60 cm (J2), and 80 cm x 60 cm (J3). The second factor was the number of fruits per plant with three levels: one fruit per plant (P1), two fruits per plant (P2), and three fruits per plant (P3). The observed parameters included weight per fruit (kg), fruit weight per plant (kg), fruit diameter (cm), flesh thickness (cm), and soluble solid content (ᵒbrix). Data analysis was performed using variance analysis followed by the LSD test at 5%. The results showed that a plant spacing of 60 cm x 60 cm with two fruits per plant and a plant spacing of 80 cm x 60 cm with two fruits per plant yielded better results for all parameters except for soluble solid content.